The Golden Book of Business Presentation Skills: Quick and Easy Tips to Make Powerful Presentations - RASMIN, La Ode; SAMSUDIN, Samsudin (Research and Innovation in Applied Linguistics, 2023)
This book is not for generic business presentation tips. However, it provides several tried-and-tested presentation elements. It will help the presenter to enlighten, influence, and excite the audience. Each chapter is segmented into â€œKnowâ€ and â€œHowâ€ sections to help you grasp the idea and use it in your business presentation. This book will help you maximize your presentations to a group, relevant stakeholders, or a digital/online presentation. For example, learning to promote yourself professionally, amaze your audience, start, end, and transition your presentation. It also includes ideas on designing a presentation outline, practicing, and presenting. This book presents eight golden steps for delivering business presentations: 1) understanding the target audienceâ€™s viewpoints, 2) mastering the topic of the presentation, 3) outlining the presentation (e.g., topics, structure, rules), 4) summarizing the presentation, 5) handling the questions effectively and straightforwardly, 6) concluding the comments and responses effectively, and 7) using both verbal and non-verbal communications effectively during the presentation., and 8) the way forward, beyond this book. A business presentation must be well-prepared and consider ways to impress the audience (Sweeney, 2003). Moreover, a presenter must have an idea to map their mind to organize their talks during the presentation (Buzan & Abbott, 2006).